Comparison the Vatican Leadership and Iran - Sayed Muhammad Dauly (International Journal on Social Science, Economics and Art, 2019)
Research is called “comparison the vatican leadership and iran”. This study attempts to tell the difference justice and equality leadership the vatican the country and iran by means of membandingan the concept of leadership the two countries . The two countries the vatican and iran have a way leadership different from different religious also, the vatican to the monarchy absolute and iran with teodemokrasi in modification with the government the clergy and modification of this touch three joints sitem repubik, covering those institutions that are commonly called triassic politika (executive, legislative, judiciary). This research using the theory sovereignty the lord and comparison political. Research methodology used is the method comparison. Technique data collection used research library (library research). As for the result of the research indicated differences and similarities the state the vatican and iran by using the theory sovereignty the lord and comparison political .Researchers perceive the difference in leadership the two countries in things up a policy .The concept of leadership the two countries have the difference , to the vatican leadership be to the pope and to the whole residents catholic of the world , different with iran the concept of imamah is at the area of the states iran itself , by one that witnesses equation for leadership the two countries the policies the state only in decided by a single person who considered people to be vice the lord in the world.